Prædikenen 31.7. 1825 og dens hidtil utrykte slutning - Thaning, Kaj (Grundtvig-studier, 1982)
Grundtvig’s Sermon for July 31st, 1825 and its unpublished ending By Kaj Thanning In his Grundtvig selection Holger Begtrup included the Sermon for July 31st, 1825, in which Grundtvig proclaimed his “unparalleled discovery” for the first time; but the ending to the sermon was missing. During a registration o f the papers it was discovered amongst a number o f drafts for the articles in Th.M. (File 113 L), and it is published here with a brief introduction by Kaj Thaning.In the sermon several themes from his work during the previous week can be traced, and thus in the ending we find his reflections on the possible conflict between the creed and the scriptures.Both discoveries can be seen in the sermon - the matrix o f the Church and the significance o f the apostolic creed, but now they are fused into one.In one o f the drafts in File 97, written after the two discoveries, Grundtvig formulates his case concisely: the questions is, “whether the Church is built on a book or a rock, whether the scriptures derive from the Word, or the Word from the scriptures, whether the Spirit is plucked out o f the air or received in baptism, whether the head lives o ff the heart or the heart o ff the head”.